Development of cordycepin formulations for preclinical and clinical studies - Lee, Jong Bong; Adrower, Cecilia; Qin, Chaolong; Fischer, Peter M.; Moor, Cornelia H. de; Gershkovich, Pavel (Springer, 2017)
There is extensive literature on in vivo studies with cordycepin but these studies were generally conducted without validation of the various formulations, especially in terms of the solubility of cordycepin in the dosing vehicles used. Cordycepin is a promising drug candidate in multiple therapeutic areas and there is a growing interest in studies aimed at assessing the pharmacological activity of this compound in relevant animal disease models. It is likely that many reported in vivo studies used formulations in which cordycepin was incompletely soluble. This can potentially confound the interpretation of pharmacokinetics and efficacy results. Furthermore, the presence of particles in intravenously administered suspension can cause adverse effects and should be avoided. Here we present the results from our development of simple and readily applicable formulations of cordycepin based on quantitative solubility assessment. Homogeneous solutions of cordycepin were prepared in phosphate-buffered saline (PBS) at different pH levels, suitable as formulations for both intravenously and oral administration. For the purpose of high-dose oral administration we also developed propylene glycol (PPG)-based vehicles in which cordycepin is completely soluble. The stability of the newly developed formulations was also assessed, as well the feasibility of their sterilisation by filtration. Additionally, an HPLC-UV method for the determination of cordycepin in the formulations, which may also be useful for other purposes, was developed and validated. Our study could provide useful information for improvement of future preclinical and clinical studies involving cordycepin.